A novel methodology to assess the scientific standing of nations at field level. Issue 1 (February 2020) - Abramo, Giovanni; D'Angelo, Ciriaco Andrea
Highlights: We introduce a novel input-output approach for measuring field performance. We apply the methodology to identify strong and weak research fields in Italy. The methodology can support the formulation of national research policies. Abstract: The formulation of national research policies would benefit greatly from reliable strategic analysis of the scientific infrastructure, aimed at identifying the relevant strengths and weaknesses at field level. Bibliometric methodologies thus far proposed in the literature are not completely satisfactory. This work proposes a novel "output-to-input-oriented" approach, which permits identification of research strengths and weaknesses on the basis of the ratios of top scientists and highly cited articles to research expenditures in each field. The proposed approach is applied to the Italian academic system. 2012–2016 scientific publications are analyzed, in the 218 research fields where bibliometric assessment is appropriate.